2022
DOI: 10.1007/s00018-022-04331-0
|View full text |Cite
|
Sign up to set email alerts
|

Mettl14 mediates the inflammatory response of macrophages in atherosclerosis through the NF-κB/IL-6 signaling pathway

Abstract: The inflammatory response of macrophages has been reported to play a critical role in atherosclerosis. The inflammatory state of macrophages is modified by epigenetic reprogramming. m6A RNA methylation is an epigenetic modification of RNAs. However, little is known about the potential roles and underlying mechanisms of m6A modification in macrophage inflammation. Herein, we showed that the expression of the m6A modification “writer” Mettl14 was increased in coronary heart disease and LPS-stimulated THP-1 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(53 citation statements)
references
References 52 publications
4
48
1
Order By: Relevance
“…METTL3 facilitates M1 macrophage polarization through m 6 A-mediated augmentation of STAT1 expression [ 211 ]. METTL14 deficiency induces M2 macrophage polarization and decreases Myd88 and IL-6 levels due to loss of m 6 A modification [ 212 ]. IGF2BP2 targets methylated TSC1 to induce macrophage polarization from the M1 to the M2 phenotype and alleviate inflammation [ 213 ].…”
Section: The M 6 a Methylation Programme In Immune...mentioning
confidence: 99%
“…METTL3 facilitates M1 macrophage polarization through m 6 A-mediated augmentation of STAT1 expression [ 211 ]. METTL14 deficiency induces M2 macrophage polarization and decreases Myd88 and IL-6 levels due to loss of m 6 A modification [ 212 ]. IGF2BP2 targets methylated TSC1 to induce macrophage polarization from the M1 to the M2 phenotype and alleviate inflammation [ 213 ].…”
Section: The M 6 a Methylation Programme In Immune...mentioning
confidence: 99%
“…Further, METTL3 and METTL14 KO inhibits M1 but not M2 macrophage polarization. Thus, these loci serve as potential anti-inflammatory targets [ 80 , 81 ].…”
Section: Epigenetic Regulation Of Macrophage Polarization and Cvdsmentioning
confidence: 99%
“…Studies have indicated that the NF-κB signaling pathway might be the key target. It has been shown that METTL14 played a vital role in macrophage inflammation in atherosclerosis via the NF-κB/IL-6 signaling pathway ( Zheng et al, 2022 ). Furthermore, METTL3 participated in sympathetic neural remodeling post-myocardial infarction (MI) via the NF-κB pathway and reactive oxygen species (ROS) production.…”
Section: Functions Of N6-methyladenosine Modification In Central Nerv...mentioning
confidence: 99%